Environmental performance of clay-based barriers for radioactive waste disposal: a review with relevance to Portuguese geological materials - Paula Galego Fernandes; M. Isabel Dias; José Marques (Annals of Nuclear Energy, 2027)

Nursery habitat use of juvenile meagre (Argyrosomus regius): findings from acoustic telemetry in the Tagus estuary - João P. Marques; Pedro R. Almeida; Nuno Prista; José Lino Costa; Carlos M. Alexandre; Catarina S. Mateus; Isabel Domingos; Patrick Reis-Santos; Bernardo R. Quintella (Marine Biology, 2026)
We used acoustic telemetry to investigate the nursery habitat use of 33 juvenile meagre Argyrosomus regius (mean size = 581 ± 105.1 mm), recording more than 60,000 detections in the Tagus estuary, located in the North-Eastern Atlantic. All individuals used the nursery area from spring to autumn, and a small number (22.2%) remained in the Tagus estuary during winter. Daily movements averaged 6.2 ± 1.9 km, with maximum daily distances reaching 41.2 ± 17.3 km. Peak movement activity was observed in July-October (average distance = 367.3 ± 240.3 km), and predominantly during the night. Furthermore, larger sized individuals returned to the Tagus estuary in subsequent years, typically using this habitat from May to October for an average of 108.5 ± 43.0 days. Spatial analyses indicated that the lower and middle sections of the Tagus estuary serve as important nursery habitats year-round, whereas the upper estuary functions as a nursery primarily from March through June. Network movement analyses highlighted that specific areas in the middle and lower reaches exhibit higher movement activity. Generalized additive modelling indicated that the occurrence of juvenile meagre in the Tagus estuary was significantly influenced by temporal and environmental variables, including day of the year, salinity, dissolved oxygen, and temperature, measured both in the estuary and in the adjacent coastal area. These findings enhance our understanding of the habitat use in estuarine nursery areas and emphasise the importance of incorporating targeted fisheries management strategies in nursery areas to promote the sustainability of this ecologically and economically important fish.

A New Challenge to Species Delimitation: Remarkable Genomic and Ecological Diversity in the Butterfly Melitaea diamina - Loukia Spilani; Valéria Marques; Cecilia Montiel‐Pantoja; Miguel Sanjurjo‐Franch; Isabel Martínez‐Pérez; Sergio Montagud Alario; Leonardo Dapporto; Vlad Dincă; Roger Vila (Molecular Ecology, 2026)
Evolution relentlessly challenges any concept of species, and human efforts to fit a taxonomic hypothesis to patterns in nature often seem unsatisfactory. Genomics show that a solution does not always come with more data: a fine‐scaled view may reveal populations with a more gradual array of differentiation, infer cases of hybrid origin and bring to light the existence of ghost populations. The false heath fritillary, Melitaea diamina , is a Palearctic butterfly with patchy, localized populations highly dependent on humid temperate habitats. Despite its extensive geographic range, populations at the southern edge of its European distribution are scarce and poorly studied genetically. Here, we employed genome‐wide data to reveal the existence of two major groups in M. diamina : an Iberian and a Eurasian lineage. Within Iberia, we documented a remarkable diversity: the populations in the Pyrenees are of hybrid origin between the Eurasian lineage and a now apparently extinct Iberian population. The ghost population was related to three extant additional Iberian lineages that align with mitochondrial differentiation, distinct morphological traits, and/or ecological specialization in the form of host plant association. Gene flow analyses suggested historical admixture despite current isolation, underscoring the complex evolutionary history of these populations. We attempt a revised taxonomic framework for this novel array of evolutionary significant units, adopting an updated subspecies concept—defining subspecies as incompletely separated lineages within a more inclusive lineage. Such an approach allows accurate representation of evolutionary complexity without prematurely elevating these populations to species rank, thereby informing targeted, biologically meaningful conservation strategies.

Pyriproxyfen and diflubenzuron pesticides impair human adipose stem cell function: evidence of redox imbalance, KDM6B upregulation, and dysregulated adipogenesis - Ana Beatriz Marques Abel; Andressa França Sousa Bispo; Jussara de Jesus Simao; Artur Francisco da Silva Neto; Julia Fernandes Barcella; Lila Missae Oyama; Bruno Fiorelini Pereira; Allain Amador Bueno; Maria Isabel Cardoso Alonso-Vale (Food and Chemical Toxicology, 2026)

Comparative proteomic analysis of Trioza erytreae nymphs developed on Citrus ×limon and Citrus ×sinensis host plants - Tomás Thormann Abranches de Magalhães; Liliana Isabel Tomé dos Anjos; Deborah Mary Power; José Alberto Cardoso Pereira; Amílcar Manuel Marreiros Duarte; Natália Tomás Marques (Arthropod-Plant Interactions, 2026)
Trioza erytreae is a vector of Huanglongbing (HLB), a highly damaging citrus disease. Lemon plants ( Citrus × limon ) are the preferred host for T. erytreae , although the underlying mechanisms behind this remain to be fully elucidated. A comparative proteomic analysis of T. erytreae nymphs in their fourth and fifth instars that were fed either lemon or sweet orange (SwO) was carried out to investigate the interaction with its hosts. A 24-hour sucrose feeding assay was conducted to understand proteomic responses to a nutrient-poor diet. Proteomic profiling using nanoscale liquid chromatography coupled to tandem mass spectrometry (nanoLC-MS/MS) identified a total of 1,477 psyllid proteins with high confidence. Oviposition and nymphal development were also evaluated across citrus hosts, revealing higher numbers of nymphs developing on lemon than on SwO. Feeding on SwO enriched pathways related to “transmission across chemical synapses” and “metabolism of proteins”. Responses observed under a 24-hour sucrose-only diet enriched the biological processes “response to external stimulus”, “response to stress” and “cytoskeleton organization”. In contrast, these enrichments were absent on lemon host, suggesting that lemon provides a more favourable environment for psyllid development. In addition, nymphs developed on lemon exhibited enhanced energy metabolism and an increase in translation initiation factors. Overall, the results demonstrate that development strongly depends on host plant species, with SwO impairing optimal growth and lemon promoting successful nymphal development.

Peptide-functionalized TiO2 nanotubes: Surface modification and preliminary in vitro cell response - Almerinda Agrelli; Rayane Cristine Santos da Silva; Priscilla Stela Santana de Oliveira; Niedja Fittipaldi Vasconcelos; Carina Lucena Mendes Marques; Isabel Renata de Souza Arruda; Mercia Oliveira; Giovanna Machado (Next Research, 2026)

Corrigendum to “Production of sustainable aviation fuel precursors using the oleaginous yeast Rhodotorula toruloides PYCC 5615 cultivated on eucalyptus bark hydrolysate” [Biomass Bioenergy 197 (2025) 107790] - Teresa Lopes da Silva; Francisca Dutra; Susana Marques; Miguel Gomes; Paula Costa; Filipe Paradela; Frederico Castelo Ferreira; Nuno Torres Faria; Paula Mugica; Helena M. Pinheiro; Isabel Sá-Correia; Francisco Gírio (Biomass and Bioenergy, 2026)

Bacillus Co-inoculation Improves the Stomatal Conductance, Root Angulation, and Harvest Index of Maize Under Water Deficit in a Line-Source Irrigation System - Diego Dias Rafael; Daniele Maria Marques; Isabel Regina Prazeres de Souza; Paulo César Magalhães; Camilo de Lelis Teixeira de Andrade; Ivanildo Evódio Marriel; Thiago Teixeira Santos; Maria Lúcia Ferreira Simeone; Thiago Corrêa de Souza (Journal of Plant Growth Regulation, 2026)
The objective of this study was to evaluate the ecophysiological and agronomic characteristics and the root morphology of maize inoculated or co-inoculated with rhizobacteria at various irrigation depths (line-source) in the field. The depths were imposed from stage V5 and continuously until the end of the cycle. The experiment was carried out in the field with seven inoculant treatments: control (no inoculation), Azospirillum brasilense , Bacillus safensis and Bacillus pumilus (BSBP), Bacillus subtilis and Bacillus megaterium (BSBM), Azospirillum brasilense + BSBP., Azospirillum brasilense + BSBM, and BSBP + BSBM, and three irrigation management methods: full irrigation depth (566 mm), suboptimal irrigation depth (423 mm), and irrigation depth with water deficit (150 mm), with four replicates. Stomatal conductance, photosynthetic efficiency, relative chlorophyll content, leaf area, production components, chemical composition of dry biomass, and root morphology were evaluated. Most inoculations or co-inoculations positively affect plant morphophysiology with a reduction in irrigation depth, but this effect is not reflected in production gains. However, co-inoculation with Bacillus subtilis and Bacillus megaterium (BSBP) was the most efficient at mitigating severe water deficit in maize because it increased stomatal conductance, root angulation, and the harvest index. Rhizobacteria have proven to constitute an ecologically correct strategy that favors root development, with the aim of mitigating the effects of water deficit in maize plants.

Exploring the diversity and distribution of Mozambique’s soft corals (Octocorallia) through an integrative approach - Bibiana Américo Fernando Nassongole; Lene Buhl-Mortensen; Isabel Marques da Silva; Ana Hilário; Catherine S. McFadden (Marine Biodiversity, 2026)
Coral reefs in the Western Indian Ocean (WIO) are experiencing continuous degradation, with projections indicating rapid disappearance due to rising sea temperatures. Mozambique has the third-largest coastline in the WIO and extensive reef areas recognized as biodiversity hotspots for tropical corals, yet many taxa remain poorly studied, especially soft corals. To address this gap, 182 colonies were collected from seven reef sites in northern and southern Mozambique using SCUBA, at depths ranging from 2.8 to 16.8 m. Species were identified using morphological and molecular phylogenetic analyses, incorporating nuclear ( 28S rDNA ) and mitochondrial ( mtMutS ) markers. A total of 63 Octocorallia species were identified along the Mozambique coast, distributed among 11 families and 23 genera, with 32 taxa unidentified at the species level. Notably, 52% of the species and 48% of the genera represent new records for Mozambique. Among these, we recorded the genus Plumigorgia for the first time in East Africa, likely representing a new species. Phylogenetic analyses revealed substantial species diversity, with many sequences not matching known records, indicating potential discoveries or the need for taxonomic revisions. Regional variations in coral communities were observed; the northern region exhibited greater diversity in growth forms, while the southern region was dominated by encrusting corals. Vamizi Island emerged as a biodiversity hotspot, hosting the highest number of families (10) and 14 genera. This study updates the soft coral fauna of Mozambique, expanding the species list from 53 to 84 and adding eleven new genera. The findings emphasize the need for continued research to support conservation and management efforts for these vital reef ecosystems.

From waste to circularity: the potential of different treatments of poultry manure and forestry residues in a hot-spot production region in Portugal - Ana d’Espiney; Bengt Verworner; Helena M. Pinheiro; Isabel P. Marques; Katja Oehmichen; Nils Engler; Stefan Majer; Walter Stinner; Daniela Thrän (The International Journal of Life Cycle Assessment, 2026)
Purpose The management of biogenic residues in a way that extends the lifetime of carbon within the systems is a focus of the present work. Different waste management systems are assessed in terms of GHG emissions and removals, aiming to identify that with the lowest impact on climate change. Methods A life cycle comparative analysis is performed, assessing the mitigation of the impact on climate change of the current waste management system (A) of the top two residues of a Portuguese region – composting of poultry manure and open air burning of forestry residues – considering two bioenergy solutions: biochemical conversion of poultry manure and thermochemical conversion of wood residues (B); biochemical conversion for both residues together (C), implying fungal pre-treatment of the wood residues, which adds a food product to the supply chain. Data were retrieved from literature and from authors’ experimental work. Assumptions underlying the methodological framework (e.g., cut offs inherent to comparative assertions) are discussed. A sensitivity analysis covers uncertainties underpinning bioenergy systems assessments (e.g., unperfect substitution and rebound effect phenomena). Results and discussion The highest impact on climate change is observed with system A, greenhouse gas (GHG) emissions 2 to 3 times higher than those of the other two systems. System A also performs poorly in conserving the biomass, e.g., forestry residues burning results in carbon being directly released to the atmosphere with no valuable intermediate use. In the base scenario, system B results in the lowest GHG emissions of the three systems, producing biochar, which contributes to carbon sequestering, and biodiesel. Nevertheless, system C can result in the lowest GHG emissions, in a scenario considering unperfect substitution with renewable sources being selected to match the biodiesel supply of system B. Conclusions System A is least preferable among the three options. Between systems B and C, ranking depends on whether unperfect substitution is considered. System B performs better in all scenarios, except with unperfect substitution, where system C outranks B. Moreover, system C achieves a higher yield of digestate, a product providing other ecosystem services. Thus, in future research, the inclusion of other impact categories in LCA can reveal a better overall environmental performance for system C.

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

ProAKAP4 as a protein marker of sperm quality: Insights from frozen-thawed ejaculated and epididymal sperm - Myrian Megumy Tsunokawa Hidalgo; Ana Beatriz Marques de Almeida; Leticia Amanda dos Santos Silva; Vinicius Wagner Silva; Julia Rodrigues Greghi; Natália Ribeiro Sambatti; Luiz Guilherme Corsi Trautwein; Rodrigo Yudi Palhaci Marubayashi; João Carlos Pinheiro Ferreira; Maria Isabel Mello Martins (Theriogenology, 2026)

In loving memory of Deolinda Flores (1958–2025) - Manuela Marques; Isabel Suárez-Ruiz; Lopo Vasconcelos; Henrique Pinheiro; João Graciano Mendonça Filho (International Journal of Coal Geology, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Cymbopogon winterianus essential oil as an alternative source for producing terpenic esters with potential plant-protective antifungal activity using lipase immobilized on a lignin composite - Carlos Alberto Chaves Girão Neto; Carolin Richter; Isabel Cristina Medeiros Prasilde; Kirley Marques Canuto; Magda Elisa Turini da Cunha; Bruno M. Moerschbacher; Tigressa Helena Soares Rodrigues; Maria Valderez Ponte Rocha (Biocatalysis and Agricultural Biotechnology, 2025)

Production and characterization of Laccase from Lentinus berteroi and applications for biodegradation of organic micropollutants - Katielle Vieira Avelino; Marisangela Isabel Wietzikoski Halabura; Edileusa Cristina Marques Gerhardt; Maira Gabriela Paetzold; Asif Khan; Juliana Silveira do Valle; Flavio Augusto Vicente Seixas (Biodegradation, 2025)

Relationship between the distribution of rare earth elements in soil pools with plant uptake: a sequential extraction study - Kaisa Forsyth; Aline Dia; Rosa Marques; Maria Isabel Prudêncio; Cynthia Obregón-Castro; Catarina Diamantino; Edgar Carvalho; Maxime Pattier; Mélanie Davranche; Mathieu Pédrot (Plant and Soil, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Modeling and spatio-temporal prediction rainfall data applied to mass movements in Belo Horizonte, Minas Gerais - Brazil - Bianca Nespoli Cortez; Jandresson Dias Pires; Gabrielle Ferreira Pires; Gérson Rodrigues Dos Santos; Marcos Barreto De Mendonça; Eduardo Antonio Gomes Marques; Nathan Ribeiro Mac Laren Nogueira; Isabel Eustáquia Queiroz Volponi (Journal of South American Earth Sciences, 2025)

Production of sustainable aviation fuel precursors using the oleaginous yeast Rhodotorula toruloides PYCC 5615 cultivated on eucalyptus bark hydrolysate - Teresa Lopes da Silva; Francisca Dutra; Susana Marques; Miguel Gomes; Paula Costa; Filipe Paradela; Frederico Castelo Ferreira; Nuno Torres Faria; Paula Mugica; Helena M. Pinheiro; Isabel Sá-Correia; Francisco Gírio (Biomass and Bioenergy, 2025)

Optimization of electro-Fenton process applied to the treatment of codfish brines in a context of industrial symbiosis - Luana Sarinho; Pedro Carvalho; Diana Patoilo; João Peres Ribeiro; Joaquim Manuel Gaião; José Baião da Cruz; Catarina Marques; Maria Isabel Nunes (Journal of Environmental Management, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

The tumor microbiome composition of non-small cell lung carcinoma correlates with expression differences in genes related with immunity, proteolysis and the extracellular matrix remodeling - Patrícia Isabel Marques; Nuno Boto Carlos; Susana Seixas (Next Research, 2025)

Length–Weight Relationship and Diet Composition of the Spotcheek Emperor, Lethrinus rubrioperculatus (Sato 1978) (Actinopterygii: Perciformes: Lethrinidae) from the Mecúfi Waters, Cabo Delgado, Mozambique - Dércio Pequenino Maoze; Vasco Long Puan; Érica Helena Tovela; Torres Armando Taimo; Abacar Raimundo Aly Amade; Carolina Marcela Mutatisse; Isabel Marques da Silva (Thalassas: An International Journal of Marine Sciences, 2025)

Effects of Amendments on Tropical Mining Soils: Geochemical, Toxicological and Microbiological Approaches - Jacqueline Zanin Lima; Jéssica Pelinsom Marques; Isabel Kimiko Sakamoto; Eduardo Ferreira da Silva; Valéria Guimarães Silvestre Rodrigues (Water, Air, & Soil Pollution, 2025)

Implementation of an IoT architecture for promoting healthy air quality in 84 homes of families with children - Marta Fonseca Gabriel; Gonçalo Marques; David Filipe; Fátima Felgueiras; João Pedro Cardoso; Joana Azeredo; Giannis Kazdaridis; Polychronis Symeonidis; Stratos Keranidis; Peter Conradie; Isabel Azevedo; Filippos Anagnostopoulos (Building and Environment, 2024)

Influence of paternal factors on plastic ingestion and brominated chemical exposure in East Tropical Atlantic Procellariid chicks - Diana M. Matos; J.A. Ramos; A.L.C. Brandão; Francisca Baptista; Isabel Rodrigues; J.O. Fernandes; L.A.E. Batista de Carvalho; M.P.M. Marques; S.C. Cunha; Stefan Antunes; V.H. Paiva (Science of The Total Environment, 2024)

Evaluation of the testicular artery Doppler velocimetry and its correlation with sperm defects in domestic cats - Luiz Guilherme Corsi Trautwein; Myrian Megumy Tsunokawa Hidalgo; Ana Beatriz Marques de Almeida; Jamile Haddad Neta; Guilherme Schiess Cardoso; Karina Keller Marques da Costa Flaiban; Vinícius Wagner Silva; Leticia Amanda dos Santos Silva; Maria Isabel Mello Martins (Animal Reproduction Science, 2024)

Environmental assessment of an innovative adhesive for the footwear industry: road map for product development - Carla L. Simões; António Aguiar; Ana C. Marques; Isabel Pinho; Ricardo Simoes (The International Journal of Life Cycle Assessment, 2024)
Purpose This work presents an environmental assessment of two adhesives to evaluate the replacement of the traditional adhesive (PU) used in the footwear industry by a novel adhesive based on a microencapsulation approach (PUMC) which is more favorable from the safety and technical perspectives. The PU adhesive is polyurethane-based, while the PUMC adhesive is polyurethane-based but with its isocyanate compounds microencapsulated, increasing storage life and reducing risks related to the exposure of workers with the adhesives. Methods The potential environmental impact of the adhesives was evaluated using the life cycle assessment (LCA) methodology. A detailed process model was developed (both for laboratory and for a pilot-scale implementation) to investigate the environmental impacts associated with these processes. The functional unit was one kilogram of adhesive (PU and PUMC adhesives) produced. A cradle-to-customers’ gate approach was defined. The system boundary starts from extraction of resources, through material production, until adhesive use. This includes microcapsule production in the case of the PUMC adhesive. This study investigates the important drivers behind the environmental impacts to help guide commercialization efforts. A scenarios study/sensitivity analysis was conducted to determine the response of the PUMC adhesive system to the variability of the model, scenarios, and parameters. Results The results show that the PU adhesive environmental impact is due to acetone and polyol consumption in the production stage. In the PUMC adhesive system, acetone consumption and microcapsule production are the major factors responsible for the environmental impact. Polybutylene adipate terephthalate (PBAT), dichloromethane (DCM), and isophorone diisocyanate (IPDI) consumption are the major factors responsible for the environmental impact of the microcapsules’ production. A sensitivity analysis was conducted using three alternative scenarios focused on the reduction in material consumption and increase in material recuperation, as well as using an alternative renewable energy source. Although the traditional PU adhesive has a lower impact, it was found that the three alternative PUMC adhesive systems can become comparable to the traditional PU adhesive. Conclusions This study shows the advance and development of a new technology for microencapsulation of isocyanate in adhesives and its environmental advantages and disadvantages with respect to a traditional product that uses non-encapsulated isocyanate. Finally, it was shown that there is significant potential for minimizing some environmental impacts of the PUMC adhesive, such as optimizing the microcapsules’ production stage, increasing the production efficiency to decrease the required material consumption.

Factors associated with behavioral changes in pet dogs during the COVID-19 pandemic in Brazil - Maria Isabel Vaz de Melo; Mayra Alves Stradioto; Gabriel Rafael Silva Gomes; Sarah Marques Santana; Letícia dos Santos Pozzato; Iara Wolbert; Paula Xavier Nogueira Costa; Angélica da Silva Vasconcellos (Journal of Veterinary Behavior, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

How can landscape visual assessment inform landscape planning and management? – Alto Douro Wine region case study, Portugal - Ana Medeiros; Cláudia Fernandes; João F. Gonçalves; Paulo Farinha-Marques; Isabel Martinho Da Silva (Applied Geography, 2024)

Snake and arthropod venoms: Search for inflammatory activity in human cells involved in joint diseases - Miryam Paola Alvarez-Flores; Isabel de Fatima Correia Batista; Isadora Maria Villas Boas; Michelle Cristiane Bufalo; Jean Gabriel de Souza; Douglas Souza Oliveira; Giuliano Bonfá; Cristina Maria Fernandes; Rafael Marques Porto; Flavio Lichtenstein; Gisele Picolo; Denise V. Tambourgi; et al. (Toxicon, 2024)

Microplastics ingestion and endocrine disrupting chemicals (EDCs) by breeding seabirds in the east tropical Atlantic: Associations with trophic and foraging proxies (δ15N and δ13C) - Diana M. Matos; J.A. Ramos; A.L.C. Brandão; Alexandra Baeta; Isabel Rodrigues; I. dos Santos; João Coentro; J.O. Fernandes; L.A.E. Batista de Carvalho; M.P.M. Marques; S.C. Cunha; S.H. Santos; et al. (Science of The Total Environment, 2024)

Living benthic foraminifera from Almirante Câmara and Grussaí canyons and adjacent slope areas (Campos Basin, Southwest Atlantic): Response to trophic and hydrodynamic conditions - Silvia Helena Mello Sousa; Cintia Yamashita; Thaisa Marques Vicente; Rafaela Nogueira Mendonça Mendes; Laetitia Licari; Maria Virgínia Alves Martins; Bianca Sung Mi Kim; Christian Millo; Renato Carreira; Isabel Montoya-Montes; Michael A. Kaminski; Michel Michaelovitch Mahiques (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Haplotype diversity patterns in Quercus suber (Fagaceae) inferred from cpDNA sequence data - Filipe Sousa; Mariana Bray Viegas; Joana Costa; Isabel Marques; Francisco Pina-Martins; Fernanda Simões; José Matos; Maria Glushkova; Célia Miguel; Maria Manuela Veloso; M. Margarida Oliveira; Cândido Pinto Ricardo; et al. (Plant Systematics and Evolution, 2023)
Chloroplast genome diversity in cork oak ( Quercus suber ) is characterised by the occurrence of haplotypes that are akin to those found in other Mediterranean oak species, particularly in Q. ilex and Q. rotundifolia , suggesting the possible presence of an introgressed chloroplast lineage. To further investigate this pattern, we reconstructed chloroplast haplotypes by sequencing four chloroplast markers (cpDNA), sampled across 181 individuals and 10 taxa. Our analyses resulted in the identification of two diversified chloroplast haplogroups in Q. suber , corresponding to a geographically widespread lineage and an Afro-Iberian lineage. Time-calibrated phylogenetic analyses of cpDNA point to a Miocene origin of the two haplogroups in Q. suber , suggesting that the Afro-Iberian lineage was present in cork oak before the onset of glaciation periods. The persistence of the two haplogroups in the western part of the species distribution range may be a consequence of either ancient introgression events or chloroplast lineage sorting, combined with different fixation in refugia through glaciation periods. Our results provide a comprehensive insight on the origins of chloroplast diversity in these ecologically and economically important Mediterranean oaks.

Geochemical Behaviour of Rare Earth Elements Throughout an Acid Mine Drainage Passive Treatment System in the Lousal Mine Area, Portugal - Cynthia Obregón-Castro; Maria Isabel Prudêncio; Catarina Diamantino; Edgar Carvalho; Dulce Russo; Rosa Marques (Mine Water and the Environment, 2023)
A passive remediation system was installed between 2010 and 2015 at the Lousal legacy mine site in southwestern Portugal to minimize the impact of AMD. This is the first study of the geochemical behaviour of rare earth elements (REE) in the area after implementation of the passive treatment system. The total and dissolved concentrations of REE is similar throughout the basins/wetlands and acidic ponds in both sampling campaigns, which is mainly attributed to the conservative behaviour of these elements in acidic water. In areas where mixing of acidic and circumneutral water occurs, the REE were partially removed from solution by adsorption onto newly formed Al and Fe precipitates. Sorption onto the precipitates varies between the rare earths, with a preferential fixation of heavy REE (HREE) compared to the light REE (LREE). The normalized distribution patterns exhibit the characteristic convex-up enrichment in middle rare earth elements for AMD and display an enrichment of LREE relative to HREE in areas where mixing of waters occurs, and the pH is close to circumneutral.

Measuring healthy ageing: current and future tools - Nádia Silva; Ana Teresa Rajado; Filipa Esteves; David Brito; Joana Apolónio; Vânia Palma Roberto; Alexandra Binnie; Inês Araújo; Clévio Nóbrega; José Bragança; Pedro Castelo-Branco; Raquel P. Andrade; et al. (Biogerontology, 2023)
Human ageing is a complex, multifactorial process characterised by physiological damage, increased risk of age-related diseases and inevitable functional deterioration. As the population of the world grows older, placing significant strain on social and healthcare resources, there is a growing need to identify reliable and easy-to-employ markers of healthy ageing for early detection of ageing trajectories and disease risk. Such markers would allow for the targeted implementation of strategies or treatments that can lessen suffering, disability, and dependence in old age. In this review, we summarise the healthy ageing scores reported in the literature, with a focus on the past 5 years, and compare and contrast the variables employed. The use of approaches to determine biological age, molecular biomarkers, ageing trajectories, and multi-omics ageing scores are reviewed. We conclude that the ideal healthy ageing score is multisystemic and able to encompass all of the potential alterations associated with ageing. It should also be longitudinal and able to accurately predict ageing complications at an early stage in order to maximize the chances of successful early intervention.

Anthropogenic debris ingestion in a tropical seabird community: Insights from taxonomy and foraging distribution - D.M. Matos; J.A. Ramos; Filipa Bessa; Vítor Silva; Isabel Rodrigues; Stefan Antunes; I. dos Santos; João Coentro; A.L.C. Brandão; L.A.E. Batista de Carvalho; M.P.M. Marques; Sara Santos; et al. (Science of The Total Environment, 2023)

Treatment of salt from hides curing stage by electrocoagulation for use in the pickling stage of the tanning industry - Luana Sarinho; Pedro Carvalho; Diana Patoilo; João Peres Ribeiro; José Baião da Cruz; Joaquim Gaião; Catarina Marques; Maria Isabel Nunes (Environmental Research, 2023)

Can saline preconditioning enhance plant survival in degraded soils? Physiological, biochemical, and molecular responses in Casuarina glauca saplings - Ines Laamari; Isabel Marques; Ana I. Ribeiro-Barros; Zoubeir Béjaoui; Mejda Abassi (Plant Ecology, 2023)

Relationship between edaphoclimatic attributes and productivity of loblolly pine (Pinus taeda L.) in southern Brazil - Carolina Benghi Pinto; Renato Marques; Cilmar Antônio Dalmaso; Matheus Severo de Souza Kulmann; Isabel Deliberali; Mauro Valdir Schumacher; Jairo Calderari de Oliveira Junior (Forest Ecology and Management, 2023)

Silver nanoparticles and silver ions indistinguishably decrease sperm motility in Pacific oysters (Magallana gigas) after short-term direct exposure - Fátima Fernández-García; Ana Carvalhais; Ana Marques; Isabel B. Oliveira; Sofia Guilherme; Helena Oliveira; Catarina C.V. Oliveira; Elsa Cabrita; Juan F. Asturiano; Mário Pacheco; Cláudia Mieiro (Environmental Toxicology and Pharmacology, 2023)

Farming for nature in the Montado: the application of ecosystem services in a results-based model - M. Helena Guimarães; Teresa Pinto-Correia; Maria de Belém Costa Freitas; Isabel Ferraz-de-Oliveira; Elvira Sales-Baptista; José Francisco Ferragolo da Veiga; J. Tiago Marques; Carla Pinto-Cruz; Carlos Godinho; Anabela D.F. Belo (Ecosystem Services, 2023)

A facile blow spinning technique for green cellulose acetate/polystyrene composite separator for flexible energy storage devices - Amjid Rafique; Inês Sequeira; Ana Sofia Bento; Mariana Peyro Moniz; João Carmo; Eduardo Oliveira; João Pedro Oliveira; Ana Marques; Isabel Ferreira; Ana Catarina Baptista (Chemical Engineering Journal, 2023)

Metal mobility and bioaccessibility from cyanide leaching heaps in a historical mine site - Carlos Ruiz Cánovas; Raúl Moreno González; Bruno J.C. Vieira; Joao Carlos Waerenborgh; Rosa Marques; Francisco Macías; María Dolores Basallote; Manuel Olias; Maria Isabel Prudencio (Journal of Hazardous Materials, 2023)

Impact of climate changes in the suitable areas for Coffea arabica L. production in Mozambique: Agroforestry as an alternative management system to strengthen crop sustainability - Crimildo T. Cassamo; David Draper; Maria M. Romeiras; Isabel Marques; Rogério Chiulele; Marisa Rodrigues; Marc Stalmans; Fábio L. Partelli; Ana Ribeiro-Barros; José C. Ramalho (Agriculture, Ecosystems & Environment, 2023)

Integrated Geochemical and Mineralogical Investigation of Soil from the Volcanic Fogo Island (Cape Verde): Implications for Ecological and Probabilistic Human Health Risks - Marina MS Cabral-Pinto; Narottam Saha; C. M. Ordens; Denise Pitta-Grós; Gelson Carlos; Pedro Dinis; Rosa Marques; Isabel Prudêncio; Fernando Rocha; Eduardo A Ferreira da Silva (Exposure and Health, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Rare earth elements as statistical sentinels of pollution and paleoenvironments?: Application to a highly polluted estuary in southwestern Spain - Verónica Romero; Francisco Ruiz; María Isabel Prudencio; Juan Manuel Muñoz; Joaquín Rodríguez Vidal; Paula Gómez; Manuel Abad; Tatiana Izquierdo; María Isabel Dias; Rosa Marques; Ana Luisa Rodrigues; Luis Miguel Cáceres; et al. (Marine Pollution Bulletin, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Chickpea (Cicer arietinum L.) Seeds as a Reservoir of Endophytic Plant Growth-Promoting Bacteria - Sara S. Laranjeira; Isabel G. Alves; Guilhermina Marques (Current Microbiology, 2022)

Ambient vibration testing and seismic fragility analysis of masonry building aggregates - Vasco Miguel Serrano Bernardo; Alfredo Peres de Noronha Campos Costa; Paulo José de Oliveira Xavier Candeias; Aníbal Guimarães da Costa; Ana Isabel Mera Marques; Alexandra Rodrigues Carvalho (Bulletin of Earthquake Engineering, 2022)

Using Oyster Shells for Customized 3-D Structures for Monitoring Ecosystem Shifts on Ascidians Diversity - Luisa Marques; Guilherme Teixeira; Ricardo Calado; Ana Isabel Lillebø (Frontiers in Marine Science, 2022)
Biofouling communities are broadly distributed and there is a growing need to understand, monitor, and prevent their dispersal and colonization. Ascidians are a major group of fouling organisms but have remained poorly studied in this context. Furthermore, the search for improved sustainable practices regarding shipping networks, biofouling management, treatments, and monitorization has made headway rapidly. The present study surveyed and established a baseline for the ascidian biofouling community in a coastal lagoon, by operationalizing the concept of artificial substrate units (ASU) through a customized 3-D unit with the shape of a triangular-based pyramid, a nature-based structure that simulates natural habitats, made with oyster shells sourced from local aquaculture farms. The ASU were grouped into a five-replicate star-shaped, to be collected at each sampling moment. Throughout the 295 days (from May to December of 2020) of the present study covering five different locations of Ria de Aveiro (Portugal) coastal lagoon, a total of 12 species of ascidians were collected. While Ascidiella aspersa , Microcosmus sp., and Molgula sp. 1 were registered in all the locations surveyed, the remaining nine ascidian species were dominant only in specific locations of the coastal lagoon. Values of total abundance presented an overall increasing trend in all locations surveyed, with maximum values corresponding to summer periods. Two locations (Oyster Farm and Integrated Multi-Trophic Aquaculture Farm) recorded the highest abundance values. The present findings demonstrated that the ASU employed using oyster shells, a widely available co-product of oyster farming, can be considered an efficient support structure for short- or long-term monitoring of the ascidian community, as well as fouling communities in general. Hydrodynamics, seasonality, and nutrient-enriched waters were the main contributors to the establishment of ascidians. For the first time, Clavelina lepadiformis and A. aspersa were collected and reported in coastal waters of mainland Portugal. While preventing the settlement of fouling communities can be extremely difficult, an improved understanding of existing communities of these organisms can undoubtedly contribute to the development of improved management practices to control them. An updated list of all ascidian species recorded to date from coastal waters of mainland Portugal is also presented.

Foraging costs drive within-colony spatial segregation in shearwaters from two contrasting environments in the North Atlantic Ocean - Jorge M. Pereira; Jaime A. Ramos; Nathalie Almeida; Pedro M. Araújo; Filipe R. Ceia; Pedro Geraldes; Ana M. Marques; Diana M. Matos; Isabel Rodrigues; Ivo dos Santos; Vitor H. Paiva (Oecologia, 2022)

Spatial patterns of carnivore roadkill in a high-traffic-volume highway in the endangered Brazilian Atlantic Forest - Isabel Marques da Cruz Costa; Mariana Silva Ferreira; Claudio Lacet Belfort Mourão; Cecília Bueno (Mammalian Biology, 2022)

Potential of Ascidians as Extractive Species and Their Added Value in Marine Integrated Multitrophic Aquaculture Systems–From Pests to Valuable Blue Bioresources - Luisa Marques; Ricardo Calado; Ana Isabel Lillebø (Frontiers in Marine Science, 2022)
Ascidians are considered as filter-feeder biofouling pests that negatively affect aquaculture facilities. However, they can also be recognized as a potential co-cultured/extractive species for integrated multi-trophic aquaculture (IMTA) with potential added value as bioresources. A systematic review aiming to understand the ecological importance of ascidians as efficient filter-feeders [What?]; their potential contribution as extractive species [How?]; and to set the benchmark for their nutritional value and potential added value to the aquaculture industry [For what?] is a timely contribution to advance the state of the art on these largely overlooked bioresources. In the last two decades, there has been an overall increase in publications addressing ascidians in aquaculture, namely, their negative impacts through biofouling, as well as their role in IMTA, environmental status, and microbiology. While Ciona intestinalis , a solitary ascidian, has been the most studied species, overall, most ascidians present high filtration and fast-growth rates. As ascidians perform well under IMTA, competition for resources and space with other filter-feeders might occur, which may require additional management actions to optimize production. Studies addressing their bioactive products show that ascidians hold great potential as premium ingredients for aquafeed formulations, as well as dietary supplements (e.g., amino acids, fatty acids). Further research on the potential use of ascidians in IMTA frameworks should focus on systems carrying capacity.

Copper(II) and oxidovanadium(IV) complexes of chromone Schiff bases as potential anticancer agents - Patrique Nunes; Yasemin Yildizhan; Zelal Adiguzel; Fernanda Marques; João Costa Pessoa; Ceyda Acilan; Isabel Correia (JBIC Journal of Biological Inorganic Chemistry, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Impacts of wildfires in aquatic organisms: biomarker responses and erythrocyte nuclear abnormalities in Gambusia holbrooki exposed in situ - Ana Ré; Ana Teresa Rocha; Isabel Campos; Sérgio M. Marques; Jan Jacob Keizer; Fernando J. M. Gonçalves; Joana Luísa Pereira; Nelson Abrantes (Environmental Science and Pollution Research, 2021)

Exploring antibiotic resistance in environmental integron-cassettes through intI-attC amplicons deep sequencing - Marcela França Dias; Giovanni Marques de Castro; Magna Cristina de Paiva; Mariana de Paula Reis; Susanne Facchin; Anderson Oliveira do Carmo; Marta Salgueiro Alves; Maria Luíza Suhadolnik; Amanda de Moraes Motta; Isabel Henriques; Evanguedes Kalapothakis; Francisco Pereira Lobo; et al. (Brazilian Journal of Microbiology, 2021)

What Cancer Patients Want to Know? Questions from Oncologic Patients in a Brazilian Private Cancer Center - João Marcos Cansian; Tyana Mara Ribas D’Ávila Raymundo de Oliveira; Augusto Marques Moreira; Mariana Oliveira Tripoli de Mattos; Carla Isabel Borré; Bruno Perosa Carniel; Victória da Luz Viega Borges; Marieli Barp Ziliotto; Thais Vanessa Salvador; Thaísa Hanemann; Marco Aurélio Farina Júnior; Taiana Saraiva; et al. (Journal of Cancer Education, 2021)

Toxicity Going Nano: Ionic Versus Engineered Cu Nanoparticles Impacts on the Physiological Fitness of the Model Diatom Phaeodactylum tricornutum - Marco Franzitta; Eduardo Feijão; Maria Teresa Cabrita; Carla Gameiro; Ana Rita Matos; João Carlos Marques; Johannes W. Goessling; Patrick Reis-Santos; Vanessa F. Fonseca; Carlo Pretti; Isabel Caçador; Bernardo Duarte (Frontiers in Marine Science, 2020)
Increasing input of Metal Engineered Nano Particles (MeENPs) in marine ecosystems has raised concerns about their potential toxicity on phytoplankton. Given the lack of knowledge on MeENPs impact on these important primary producers, the effects of Copper Oxide (CuO) ENPs on growth, physiology, pigment profiles, fatty acid (FA) metabolism, and oxidative stress were investigated in the model diatom Pheodactylum tricornutum , to provide suitable biomarkers of CuO ENP exposure versus its ionic counterpart. Diatom growth was inhibited by CuO ENPs but not Ionic Cu, suggesting CuO ENP cytotoxicity. Pulse Modulated Amplitude (PAM) phenotyping evidenced a decrease in the electron transport energy flux, pointing to a reduction in chemical energy generation following CuO ENPs exposure, as well as an increase in the content of the non-functional Cu-substituted chlorophyll a (CuChl a ). A significant decrease in eicosapentaenoic acid (C20:5) associated with a significant rise in thylakoid membranes FAs reflected the activation of counteractive measures to photosynthetic impairment. Significant increase in the omega 6/omega 3 ratio, underline expectable negative repercussions to marine food webs. Increased thiobarbituric acid reactive substances reflected heightened oxidative stress by CuO ENP. Enhanced Glutathione Reductase and Ascorbate Peroxidase activity were also more evident for CuO ENPs than ionic Cu. Overall, observed molecular changes highlighted a battery of possible suitable biomarkers to efficiently determine the harmful effects of CuO ENPs. The results suggest that the occurrence and contamination of these new forms of metal contaminants can impose added stress to the marine diatom community, which could have significant impacts on marine ecosystems, namely through a reduction of the primary productivity, oxygen production and omega 6 production, all essential to sustain heterotrophic marine life.

Chronic stress decreases ornithine decarboxylase expression and protects against 1,2-dimethylhydrazine-induced colon carcinogenesis - Edgar Oswaldo Zamora-González; Patricia Castro-Félix; María del Rosario Huizar-López; Josefina Casas-Solís; María de la Luz Blanca Isabel Marques-González; Martha Fabiola Martin del Campo-Solís; Anne Santerre (Molecular Biology Reports, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Effect of Biochar on Emission of Greenhouse Gases and Productivity of Cardoon Crop (Cynara cardunculus L.) - Paulo Barracosa; Isabel Cardoso; Francisco Marques; António Pinto; Jorge Oliveira; Henrique Trindade; Pedro Rodrigues; José L. S. Pereira (Journal of Soil Science and Plant Nutrition, 2020)

The Effect of Tailored Cognitive-Behavioral Therapy for Insomnia on Brain’s Resting-State Networks - Daniel Ruivo Marques; Ana Allen Gomes; Vanda Clemente; José Moutinho dos Santos; Isabel Catarina Duarte; Gina Caetano; Miguel Castelo-Branco (Sleep and Vigilance, 2020)

Does Cognitive–Behavioral Therapy for Insomnia Change the Brain? A Case Series Study - Daniel Ruivo Marques; Ana Allen Gomes; Vanda Clemente; José Moutinho dos Santos; Isabel Catarina Duarte; Gina Caetano; Miguel Castelo-Branco (Sleep and Vigilance, 2020)

Downscaling projections of climate change in Sao Tome and Principe Islands, Africa - Sin Chan Chou; André de Arruda Lyra; Jorge Luís Gomes; Daniel Andrés Rodriguez; Minella Alves Martins; Nicole Costa Resende; Priscila da Silva Tavares; Claudine Pereira Dereczynski; Isabel Lopes Pilotto; Alessandro Marques Martins; Luís Felipe Alves de Carvalho; José Luiz Lima Onofre; et al. (Climate Dynamics, 2020)

Macroalgae-enriched diet protects gilthead seabream (Sparus aurata) against erythrocyte population instability and chromosomal damage induced by aqua-medicines - Ana Marques; Raquel Marçal; Vitória Pereira; Patrícia Pereira; Cláudia Mieiro; Sofia Guilherme; Carlos Marques; Maria Ana Santos; Rui Pereira; Helena Abreu; Isabel Gaivão; Mário Pacheco (Journal of Applied Phycology, 2020)

Relationship between substrate, physico-chemical parameters and foraminiferal tests in the Doñana National Park, a Biosphere Reserve in SW Spain - Liliana Guerra; Cristina Veiga-Pires; María Luz González-Regalado; Manuel Abad; Antonio Toscano; Juan Manuel Muñoz; Francisco Ruiz; Joaquín Rodríguez Vidal; Luis Miguel Cáceres; Tatiana Izquierdo; María Isabel Carretero; Manuel Pozo; et al. (Journal of Iberian Geology, 2020)

Applicability of water quality models around the world—a review - Cássia Monteiro da Silva Burigato Costa; Leidiane da Silva Marques; Aleska Kaufmann Almeida; Izabel Rodrigues Leite; Isabel Kaufmann de Almeida (Environmental Science and Pollution Research, 2019)

(Cyto)genomic and epigenetic characterization of BICR 10 cell line and three new established primary human head and neck squamous cell carcinoma cultures - Ilda P. Ribeiro; Joana M. Rodrigues; Alexandra Mascarenhas; Vanessa Marques; Francisco Caramelo; Maria J. Julião; Thomas Liehr; Joana B. Melo; Isabel M. Carreira (Genes & Genomics, 2019)

Cattle herd shearing can help to control Rhipicephalus microplus ticks - Cecília José Veríssimo; Rodrigo Giglioti; Selma Marques D’Agostino; Luciandra Macedo de Toledo; Luciana Morita Katiki; Keila Maria Roncato Duarte; Isabel Kinney Ferreira de Miranda Santos (Experimental and Applied Acarology, 2019)

Global Observational Needs and Resources for Marine Biodiversity - Gabrielle Canonico; Pier Luigi Buttigieg; Enrique Montes; Frank E. Muller-Karger; Carol Stepien; Dawn Wright; Abigail Benson; Brian Helmuth; Mark Costello; Isabel Sousa-Pinto; Hanieh Saeedi; Jan Newton; et al. (Frontiers in Marine Science, 2019)

Chemical characterization of vines grown in incipient volcanic soils of Fogo Island (Cape Verde) - Rosa Marques; Maria Isabel Prudêncio; Maria Manuela Abreu; Dulce Russo; José G. Marques; Fernando Rocha (Environmental Monitoring and Assessment, 2019)

Ruminal Microbial Populations and Fermentation Characteristics in Beef Cattle Grazing Tropical Forage in Dry Season and Supplemented with Different Protein Levels - Renata Pereira da Silva-Marques; Joanis Tilemahos Zervoudakis; Luciano Nakazato; Luciana Keiko Hatamoto-Zervoudakis; Luciano da Silva Cabral; Núbia Bezerra do Nascimento Matos; Maria Isabel Leite da Silva; Andresa Lazzarotto Feliciano (Current Microbiology, 2019)

Quantitative qPCR Analysis of Ruminal Microorganisms in Beef Cattle Grazing in Pastures in the Rainy Season and Supplemented with Different Protein Levels - Renata Pereira da Silva-Marques; Joanis Tilemahos Zervoudakis; Luciano Nakazato; Luciano da Silva Cabral; Luciana Keiko Hatamoto-Zervoudakis; Maria Isabel Leite da Silva; Núbia Bezerra do Nascimento Matos; Letícia Camara Pitchenin (Current Microbiology, 2018)

Climate Change Impacts on Seagrass Meadows and Macroalgal Forests: An Integrative Perspective on Acclimation and Adaptation Potential - Bernardo Duarte; Irene Martins; Rui Rosa; Ana R. Matos; Michael Y. Roleda; Thorsten B. H. Reusch; Aschwin H. Engelen; Ester A. Serrão; Gareth A. Pearson; João C. Marques; Isabel Caçador; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2018)

Beneficial effects of seaweeds from the Portuguese coast in Drosophila melanogaster life history traits – insights on the health benefits of seaweeds consumption. - João Miguel Ferreira; Ana Margarida Marques; Maria Helena Abreu; Rui Pedro Pereira; Andreia Rego; Mário Pacheco; Isabel Gaivão (Frontiers in Marine Science, 2018)

Hg-Planktarctic - Unravelling the metabolic adaptations in phytoplankton continuously exposed to volcanic-mercury in Deception Island waters (Antarctica) - Bernardo Duarte; Carlos Cordeiro; Marta Sousa Silva; Andreia Figueiredo; Rui Rosa; João Canário; Isabel Caçador; João Marques; Maria Teresa Cabrita; Ana Rita Matos; Carla Gameiro (Frontiers in Marine Science, 2018)

In Vivo Paracoccidioides sp. Biofilm on Vascular Prosthesis - Maria Emilia Cattana; Maria Fernanda Tracogna; Isabel Marques; Florencia Rojas; Mariana Fernández; María de los Ángeles Sosa; Javier Mussin; Gustavo Giusiano (Mycopathologia, 2017)

Natural Radionuclides, Rare Earths and Heavy Metals Transferred to the Wild Vegetation Covering a Phosphogypsum Stockpile at Barreiro, Portugal - José Alberto Gil Corisco; Jan Mihalík; Maria José Madruga; Maria Isabel Prudêncio; Rosa Marques; Marta Santos; Mário Reis (Water, Air, & Soil Pollution, 2017)

DNA Sequencing as a Tool to Monitor Marine Ecological Status - Kelly D. Goodwin; Luke R. Thompson; Bernardo Duarte; Tim Kahlke; Andrew R. Thompson; João C. Marques; Isabel Caçador (Frontiers in Marine Science, 2017)

Chemical element accumulation in tree bark grown in volcanic soils of Cape Verde—a first biomonitoring of Fogo Island - Rosa Marques; Maria Isabel Prudêncio; Maria do Carmo Freitas; Maria Isabel Dias; Fernando Rocha (Environmental Science and Pollution Research, 2017)

Unbalanced resting-state networks activity in psychophysiological insomnia - Daniel Ruivo Marques; Ana Allen Gomes; Vanda Clemente; José Moutinho dos Santos; Isabel Catarina Duarte; Gina Caetano; Miguel Castelo-Branco (Sleep and Biological Rhythms, 2017)

Genomic landscape of early ecological speciation initiated by selection on nuptial colour - David Alexander Marques; Kay Lucek; Marcel Philipp Haesler; Anna Fiona Feller; Joana Isabel Meier; Catherine E. Wagner; Laurent Excoffier; Ole Seehausen (Molecular Ecology, 2017)
Ecological speciation is the evolution of reproductive isolation as a consequence of direct divergent natural selection or ecologically mediated divergent sexual selection. While the genomic signature of the former has been extensively studied in recent years, only few examples exist for genomic differentiation where environment‐dependent sexual selection has played an important role. Here, we describe a very young (~90 years old) population of threespine sticklebacks exhibiting phenotypic and genomic differentiation between two habitats within the same pond. We show that differentiation among habitats is limited to male throat colour and nest type, traits known to be subject to sexual selection. Divergence in these traits mirrors divergence in much older benthic and limnetic stickleback species pairs from North American west coast lakes, which also occur in sympatry but are strongly reproductively isolated from each other. We demonstrate that in our population, differences in throat colour and breeding have been stable over a decade, but in contrast to North American benthic and limnetic stickleback species, these mating trait differences are not accompanied by divergence in morphology related to feeding, predator defence or swimming performance. Using genomewide SNP data, we find multiple genomic islands with moderate differentiation spread across several chromosomes, whereas the rest of the genome is undifferentiated. The islands contain potential candidate genes involved in visual perception of colour. Our results suggest that phenotypic and multichromosome genomic divergence of these morphs was driven by environment‐dependent sexual selection, demonstrating incipient speciation after only a few decades of divergence in sympatry.

Wastewater reuse: modeling chloroform formation - Anabela Rebelo; Isabel Ferra; Albertina Marques; Manuela Moreira Silva (Environmental Science and Pollution Research, 2016)

Reproductive synchrony in a diverse Acropora assemblage, Vamizi Island, Mozambique - Erwan Sola; Isabel Marques da Silva; David Glassom (Marine Ecology, 2016)
Multi‐specific synchronous spawning has never been documented for East Africa, but coral spawn‐slicks are observed annually around Vamizi Island, Northern Mozambique. We monitored gamete development in Acropora species from July 2012 to October 2013 and from August to September 2014 to describe patterns of reproductive seasonality and synchrony within and amongst species of Acropora . Gamete maturation was highly synchronized within and amongst Acropora species and culminated in multi‐specific spawning events lasting 1–3 nights in each year of the study, in late August or September. In 2013 and 2014, 50% or more of the colonies of over 50% of the species sampled prior to the spawning events had mature gametes. In all years, 91–99% colonies sampled after the spawning events had no visible gametes. The percentage of colonies with mature gametes was up to 100% for some species. In other species, the absence of mature gametes throughout the study period indicates that they might not spawn in certain years. The analysis of a 8‐year record of observations of spawn‐slicks showed that spawning generally occurred once a year for a few consecutive days between September and December, during periods of rising sea surface temperature and low wind speed and rainfall. This study is the first to quantitatively document coral reproduction in Mozambique and multi‐specific synchronous spawning off the coast of Africa. These findings contrast with the asynchronous breeding reported for Kenyan reefs and support the absence of breakdown in coral reproductive synchrony towards low latitudes.

Acquiring baseline information for successful plant translocations when there is no time to lose: the case of the neglected Critically Endangered Narcissus cavanillesii (Amaryllidaceae) - David Draper Munt; Isabel Marques; José M. Iriondo (Plant Ecology, 2016)

Development of an autonomous system for integrated marine monitoring - Magalhães Catarina; Mucha Ana Paula; Carvalho Maria; Ribeiro Hugo; Almeida Cristina; Azevedo Isabel; Ramos Sandra; Borges Teresa; Leandro Sérgio; Dos Santos Antonina; Silva Alexandra; Bartilotti Cátia; et al. (Frontiers in Marine Science, 2016)

Sea level rise impacts on estuarine salt marshes - a multi-disciplinary approach - Duarte Bernardo; Marques João; Caçador Isabel (Frontiers in Marine Science, 2016)

Unraveling the interactive effects of climate change and oil contamination on laboratory‐simulated estuarine benthic communities - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rui J. M. Rocha; Ricardo Calado; José M. Castanheira; Sílvia M. Rocha; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Ana I. Lillebø; Adelaide Almeida; Ângela Cunha; et al. (Global Change Biology, 2015)
There is growing concern that modifications to the global environment such as ocean acidification and increased ultraviolet radiation may interact with anthropogenic pollutants to adversely affect the future marine environment. Despite this, little is known about the nature of the potential risks posed by such interactions. Here, we performed a multifactorial microcosm experiment to assess the impact of ocean acidification, ultraviolet B (UV‐B) radiation and oil hydrocarbon contamination on sediment chemistry, the microbial community (composition and function) and biochemical marker response of selected indicator species. We found that increased ocean acidification and oil contamination in the absence of UV‐B will significantly alter bacterial composition by, among other things, greatly reducing the relative abundance of Desulfobacterales , known to be important oil hydrocarbon degraders. Along with changes in bacterial composition, we identified concomitant shifts in the composition of oil hydrocarbons in the sediment and an increase in oxidative stress effects on our indicator species. Interestingly, our study identifies UV‐B as a critical component in the interaction between these factors, as its presence alleviates harmful effects caused by the combination of reduced pH and oil pollution. The model system used here shows that the interactive effect of reduced pH and oil contamination can adversely affect the structure and functioning of sediment benthic communities, with the potential to exacerbate the toxicity of oil hydrocarbons in marine ecosystems.

Germline CDKN2A mutations in Brazilian patients of hereditary cutaneous melanoma - Alexandre Leon Ribeiro de Ávila; Ana Cristina Victorino Krepischi; Luciana Facure Moredo; Talita Ferreira Marques Aguiar; Felipe Carneiro da Silva; Bianca Costa Soares de Sá; Amanda França de Nóbrega; Maria Isabel Waddington Achatz; João Pedreira Duprat; Gilles Landman; Dirce Maria Carraro (Familial Cancer, 2014)

Autoimmune diseases association study with the KIAA1109–IL2–IL21 region in a Tunisian population - Dorra Bouzid; Hajer Fourati; Ali Amouri; Isabel Marques; Olfa Abida; Nabil Tahri; Carlos Penha-Gonçalves; Hatem Masmoudi (Molecular Biology Reports, 2014)

Anticancer activity of structurally related ruthenium(II) cyclopentadienyl complexes - Leonor Côrte-Real; Filipa Mendes; Joana Coimbra; Tânia S. Morais; Ana Isabel Tomaz; Andreia Valente; M. Helena Garcia; Isabel Santos; Manuel Bicho; Fernanda Marques (JBIC Journal of Biological Inorganic Chemistry, 2014)

Microalgae Versus Land Crops as Feedstock for Biodiesel: Productivity, Quality, and Standard Compliance - Iracema Andrade Nascimento; Sheyla Santa Izabel Marques; Iago Teles Dominguez Cabanelas; Gilson Correia de Carvalho; Maurício A. Nascimento; Carolina Oliveira de Souza; Janice Isabel Druzian; Javid Hussain; Wei Liao (BioEnergy Research, 2014)

Development and validation of an experimental life support system for assessing the effects of global climate change and environmental contamination on estuarine and coastal marine benthic communities - Francisco J. R. C. Coelho; Rui J. M. Rocha; Ana C. C. Pires; Bruno Ladeiro; José M. Castanheira; Rodrigo Costa; Adelaide Almeida; Ângela Cunha; Ana Isabel Lillebø; Rui Ribeiro; Ruth Pereira; Isabel Lopes; et al. (Global Change Biology, 2013)
An experimental life support system ( ELSS ) was constructed to study the interactive effects of multiple stressors on coastal and estuarine benthic communities, specifically perturbations driven by global climate change and anthropogenic environmental contamination. The ELSS allows researchers to control salinity, pH , temperature, ultraviolet radiation ( UVR ), tidal rhythms and exposure to selected contaminants. Unlike most microcosms previously described, our system enables true independent replication (including randomization). In addition to this, it can be assembled using commercially available materials and equipment, thereby facilitating the replication of identical experimental setups in different geographical locations. Here, we validate the reproducibility and environmental quality of the system by comparing chemical and biological parameters recorded in our ELSS with those prevalent in the natural environment. Water, sediment microbial community and ragworm (the polychaete Hediste diversicolor ) samples were obtained from four microcosms after 57 days of operation. In general, average concentrations of dissolved inorganic nutrients ( NO 3 − ; NH 4 + and PO 4 −3 ) in the water column of the ELSS experimental control units were within the range of concentrations recorded in the natural environment. While some shifts in bacterial community composition were observed between in situ and ELSS sediment samples, the relative abundance of most metabolically active bacterial taxa appeared to be stable. In addition, ELSS operation did not significantly affect survival, oxidative stress and neurological biomarkers of the model organism Hediste diversicolor . The validation data indicate that this system can be used to assess independent or interactive effects of climate change and environmental contamination on benthic communities. Researchers will be able to simulate the effects of these stressors on processes driven by microbial communities, sediment and seawater chemistry and to evaluate potential consequences to sediment toxicity using model organisms such as Hediste diversicolor .

Screening Microalgae Strains for Biodiesel Production: Lipid Productivity and Estimation of Fuel Quality Based on Fatty Acids Profiles as Selective Criteria - Iracema Andrade Nascimento; Sheyla Santa Izabel Marques; Iago Teles Dominguez Cabanelas; Solange Andrade Pereira; Janice Isabel Druzian; Carolina Oliveira de Souza; Daniele Vital Vich; Gilson Correia de Carvalho; Maurício Andrade Nascimento (BioEnergy Research, 2013)

Spatial–temporal patterns of flowering asynchrony and pollinator fidelity in hybridizing species of Narcissus - Isabel Marques; Javier Fuertes Aguilar; Maria Amélia Martins-Loução; Gonzalo Nieto Feliner (Evolutionary Ecology, 2012)

After-effects of consecutive sessions of transcranial direct current stimulation (tDCS) in a rat model of chronic inflammation - Gabriela Laste; Wolnei Caumo; Lauren Naomi Spezia Adachi; Joanna Ripoll Rozisky; Isabel Cristina de Macedo; Paulo Ricardo Marques Filho; Wania Aparecida Partata; Felipe Fregni; Iraci L. S. Torres (Experimental Brain Research, 2012)

Electron transfer between periplasmic formate dehydrogenase and cytochromes c in Desulfovibrio desulfuricans ATCC 27774 - Sofia Marques da Silva; Isabel Pacheco; Inês A. Cardoso Pereira (JBIC Journal of Biological Inorganic Chemistry, 2012)

Nuclear targeting with cell-specific multifunctional tricarbonyl M(I) (M is Re, 99mTc) complexes: synthesis, characterization, and cell studies - Teresa Esteves; Fernanda Marques; António Paulo; José Rino; Prasant Nanda; C. Jeffrey Smith; Isabel Santos (JBIC Journal of Biological Inorganic Chemistry, 2011)

Chromosome 5 derived small supernumerary marker: towards a genotype/phenotype correlation of proximal chromosome 5 imbalances - Joana Barbosa Melo; Liesbeth Backx; Joris R. Vermeesch; Heloisa G. Santos; Ana C. Sousa; Nadezda Kosyakova; Anja Weise; Ferdinand von Eggeling; Thomas Liehr; Isabel Marques Carreira (Journal of Applied Genetics, 2011)

Spartina maritima influence on the dynamics of the phosphorus sedimentary cycle in a warm temperate estuary (Mondego estuary, Portugal) - Ana Isabel Lillebø; J. P. Coelho; M. R. Flindt; H. S. Jensen; J. C. Marques; C. B. Pedersen; M. A. Pardal (Hydrobiologia, 2007)

153Sm and 166Ho complexes with tetraaza macrocycles containing pyridine and methylcarboxylate or methylphosphonate pendant arms - Fernanda Marques; Krassimira P. Guerra; Lurdes Gano; Judite Costa; M. Paula Campello; Lus M. P. Lima; Rita Delgado; Isabel Santos (JBIC Journal of Biological Inorganic Chemistry, 2004)

Comparison of phenotypic and genotypic taxonomic methods for the identification of dairy enterococci - Paula Isabel Alves; Maria Paula Martins; Teresa Semedo; José Joaquim Figueiredo Marques; Rogério Tenreiro; Maria Teresa Barreto Crespo (Antonie van Leeuwenhoek, 2004)